QUANTITATIVE ASSESSMENT OF SKIN STIFFNESS AND THICKNESS USING HIGH-FREQUENCY ULTRASOUND AND SHEAR WAVE ELASTOGRAPHY IN THE MANAGEMENT OF SCLERODERMA: A PROSPECTIVE COMPARATIVE STUDY - BASABOINA, SUDHA MADHURI; DESHNENI, NIKHIL (International Journal of Current Pharmaceutical Research, 2026)
Objective: The objective of this study is to analyze skin stiffness and thickness quantitatively in patients with systemic sclerosis using high-frequency ultrasound (HFUS) and shear wave elastography (SWE), and to compare those results with healthy controls. This study aims to examine the diagnostic utility, examine the performance between both modalities and determine their correlation with modified Rodnan skin score (mRSS), and establish their clinical utility in the early diagnosis and monitoring of disease severity in scleroderma. Methods: In this observational study, skin stiffness and thickness were assessed in SSc patients and matched healthy controls using HFUS and SWE. Quantitative measurements were taken at standard anatomical sites. Receiver operating characteristic (ROC) curve analysis evaluated the diagnostic accuracy of each modality, while correlation with the modified Rodnan skin score (mRSS) was analyzed to determine clinical relevance. Results: Both skin thickness and stiffness were significantly elevated in SSc patients compared to controls (p<0.001). SWE exhibited superior diagnostic accuracy (AUC 0.881) compared to HFUS (AUC 0.795), with sensitivities of 90% and 82%, respectively. Strong positive correlations were observed between imaging parameters and mRSS (r = 0.758 for SWE stiffness; r = 0.642 for HFUS thickness). Conclusion: HFUS and SWE constitute effective, complementary tools for quantitative evaluation of skin involvement in systemic sclerosis. Their combined use improves diagnostic precision and correlates well with clinical skin scores, supporting integration into routine clinical assessment and trials. Further multicenter validation and protocol standardization are warranted.